Collaborative Goverment Sebagai Bentuk Pencegahan Terjadinya Patologi Birokrasi Dalam Penyelengaraan Pelayanan Publik - Wihda Maulani; Maulida Putri Rahmawati (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
Quality public service is a service provided in accordance with the expectations and needs of the community as service users. One of the main roles in the implementation of public services is the bureaucracy, where the bureaucracy is also a way for the government to implement policies that are generally related to the function of public services. In the implementation of public services, there are bureaucratic pathologies that can reduce the quality of public services and harm the community. This study aims to examine the concept of collaborative governance as one way to prevent bureaucratic pathologies in the implementation of public services. The methodology of this research uses a literature review method. Collaborative governance is a concept of a collaborative pattern that involves various parties outside the government to work together in creating effective decision-making and achieving a common goal. The collaborative model can reduce bureaucratic inefficiency and the involvement of other parties from the private sector is an important element in the provision of public service facilities. The benefits of collaborative governance in improving public services are reflected in three main aspects: transparency, innovation and efficiency. Collaborative governance plays a crucial role in public service reform through multi-stakeholder integration (government, private sector, and civil society) to create innovation, transparency, and inclusivity.